Розв’язання задач управління екологічною безпекою за умови реалізації концепції корпораційної екологічної системи - Kozulja, T. V.; Sharonova, N. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
Theoretical practical basis of forming the estimations of anthropogenic loaded territories ecological risk and population health state rating on the corporative basis of research system forming are given. Corporative ecological system (CES) concept advantages are determined. The calculations of risk on the basis of a thermodynamic condition of the research objects are given.